Finding out About Everyday Things - Humberstone, Eliot; Illustrated by Nevett, Louise (London Usborne Publishing, 1981)
Picture information books to help answer young children's questions about the world around them
Include Colour Illustrations and Index
Keywords: Technology -- Science--Experiments